Profile in occupational counselling and placement and employment services: social policies axis - Roncoroni, Matilde (2002)
This paper presents the gestation of a new model of Occupational Counselling, centred in the joint action of State, Third Sector and Private Organizations. Different programmes are identified which involve the treatment of issues related to Labour, Employment and Education within the framework of objectives of social development, community participation and respect for diversity. The data of the investigation make it possible to establish connections between the tasks, professional profiles and professional training of the counsellors who participate in the different programmes.